2020
DOI: 10.3390/ncrna6010011
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1 Long Isoform Is Highly Expressed in Chronic Lymphocytic Leukemia Irrespectively of Cytogenetic Groups or Clinical Outcome

Abstract: The biological role and therapeutic potential of long non-coding RNAs (lncRNAs) in chronic lymphocytic leukemia (CLL) are still open questions. Herein, we investigated the significance of the lncRNA NEAT1 in CLL. We examined NEAT1 expression in 310 newly diagnosed Binet A patients, in normal CD19+ B-cells, and other types of B-cell malignancies. Although global NEAT1 expression level was not statistically different in CLL cells compared to normal B cells, the median ratio of NEAT1_2 long isoform and global NEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…However, few research studies focus on the upstream regulation of lncRNAs. Recently, m6A modification has become an epigenetic hot point ( 11 ). Therefore, in the current study, we explored the regulatory axis of NEAT1 in CML and ulteriorly investigated the upstream modification of NEAT1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few research studies focus on the upstream regulation of lncRNAs. Recently, m6A modification has become an epigenetic hot point ( 11 ). Therefore, in the current study, we explored the regulatory axis of NEAT1 in CML and ulteriorly investigated the upstream modification of NEAT1.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA nuclear enriched abundant transcript 1 (NEAT1) is an essential structural component of the subnuclear structure paraspeckle (8) and is closely related to malignant tumors and innate immunity (9). NEAT1 is demonstrated to be involved in acute promyelocytic leukemia (APL), acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), and also CML (9)(10)(11)(12). However, its role in CML is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, NEAT1 has been reported as deregulated in neurodegenerative diseases [ 11 ] and in the majority of tumors [ 2 ] and is known to be a direct target of the transcription factor p53 that, as is common and established knowledge, is defined as the guardian of the genome [ 3 , 4 , 50 , 51 , 52 ]. Based on these considerations, further studies will be important to unravel more precise mechanisms of NEAT1 involvement in genome integrity control and maintenance, which could likely provide a rationale for the development of NEAT1-based therapeutic options in human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…NEAT1 has been identified and validated as a p53 target by several studies that also pointed out the impairment of DDR efficiency in NEAT1 depleted cells [ 3 , 4 , 50 , 51 , 52 ]. In detail, in 2015 Blume et al reported that the induction of NEAT1 in chronic lymphocytic leukemia (CLL) primary cells could play a role in the DNA damage pathway [ 4 ], demonstrating that, after DNA damage, NEAT1 is induced in the presence of functional p53 but not in CLL carrying p53 mutation, and that its induction is closely related to cell death upon DNA damage [ 4 ].…”
Section: Involvement Of Neat1 In Dna Damage Responsementioning
confidence: 99%
“…Conversely, the expression of lincRNA‐p21 is significantly reduced in CLL patients, and low expression of this lncRNA demarcates a more aggressive form of CLL with a poor prognosis 15 . LincRNA‐p21 and the paraspeckle‐enriched lncRNA NEAT1 are involved in the induction of cell death after DNA damage 16 ; however, we recently observed that the expression of NEAT1 is quite heterogeneous in B cells derived from CLL patients irrespectively of cytogenetic groups or clinical outcome 17 …”
Section: Introductionmentioning
confidence: 99%